2017
DOI: 10.1007/s00464-017-5696-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the outcome of magnetic sphincter augmentation for chronic gastroesophageal reflux disease

Abstract: Magnetic sphincter augmentation results in excellent/good outcomes in most patients but a higher BMI, structurally defective sphincter, and elevated LES residual pressure may prevent this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The results of the feasibility, pivotal, and FDA post-approval studies have shown that magnetic sphincter augmentation is highly effective in reducing typical GERD symptoms, reducing daily PPI dependence, improving patients' quality of life, and decreasing esophageal acid exposure. 12,20 The results of the present study demonstrate a similarly high degree of symptom control, improvement in quality of life, and liberation from antisecretory medication use. MSA is comparable with LNF in the control of GERD symptoms while limiting procedure-related side effects, 12 and therefore may provide a solution to the deficits experienced with the established medical and surgical GERD therapies.…”
Section: Discussionsupporting
confidence: 64%
“…The results of the feasibility, pivotal, and FDA post-approval studies have shown that magnetic sphincter augmentation is highly effective in reducing typical GERD symptoms, reducing daily PPI dependence, improving patients' quality of life, and decreasing esophageal acid exposure. 12,20 The results of the present study demonstrate a similarly high degree of symptom control, improvement in quality of life, and liberation from antisecretory medication use. MSA is comparable with LNF in the control of GERD symptoms while limiting procedure-related side effects, 12 and therefore may provide a solution to the deficits experienced with the established medical and surgical GERD therapies.…”
Section: Discussionsupporting
confidence: 64%
“…9,10 Currently, there is a large body of literature outlining the clinical outcomes of the Nissen procedure and the patient population where it is most likely to be successful. 11,12 However, to date, there has been no large single-institution data set outlining the clinical outcomes of patients who underwent MSA when used in a "real-world" application across the spectrum of disease severity. In addition, there is a paucity of data on identifying preoperative factors that predict successful outcomes after MSA.…”
Section: Resultsmentioning
confidence: 99%
“…). A total of 39 full‐text papers, published between 2008 and 2019, were finally included. The 39 articles consisted of one RCT, five comparative cohort studies (2 prospective and 3 retrospective), three comparative case–control studies, 25 case series (14 prospective, 11 retrospective) and five case reports ( Fig .…”
Section: Resultsmentioning
confidence: 99%